Agreement and validity of electronic patient self-triage (eTriage) with nurse triage in two UK emergency departments: a retrospective study. (February 2022) - Dickson, Sarah J.; Dewar, Colin; Richardson, Amelia; Hunter, Alex; Searle, Steve; Hodgson, Luke E.
Abstract : Background: Triage and redirection of patients to alternative care providers is one tool used to overcome the growing issue of crowding in emergency departments (EDs). Electronic patient self-triage (eTriage) may reduce waiting times and required face-to-face contact. There are limited studies into its efficacy, accuracy and validity in an ED setting. Objectives: The aim of this study was to assess the agreement and validity of eTriage with a reference standard of nurse face-to-face triage. A secondary aim was to assess the ability of both systems to predict high and low acuity outcomes. Design: This was a retrospective study conducted over 8 months in two UK hospitals. Inclusion criteria were all ambulatory patients aged ≥18. All patients completed an eTriage and nurse-led triage using the Manchester Triage System (MTS). Main Results: During the study period, 43 788 adult patients attended one of the two ED sites and 26 757 used eTriage. A total of 1424 patient episodes had no recorded MTS and were excluded from the study leaving 25 333 paired triages for the final cohort. Agreement between eTriage and nurse triage was low with a weighted Kappa coefficient of 0.14 (95% CI, 0.14–0.15) with an associated weak positive correlation (rs 0.321). Level of undertriage by eTriage compared with nurse triage was 10.1%, and overtriage was 59.2%. The sensitivity for prediction of high acuity outcomes was 88.5% (95% CI, 77.9–95.3%) for eTriage and 53.8% (95% CI 41.1–66.0%) for nurse MTS. The specificity for predicting low risk patients was 88.5% (95% CI, 87.4–89.5%) for eTriage and 80.6% (95% CI, 79.3–81.8%) for nurse MTS. Conclusion: Agreement and correlation of eTriage with the reference standard of nurse MTS was low; patients using eTriage tended to over triage when compared to the triage nurse. eTriage had a higher sensitivity for high acuity presentations and demonstrated similar specificity for low acuity presentations when compared to triage nurse MTS. Further work is necessary to validate eTriage as a potential tool for safe redirection of ED attenders to alternative care providers. Abstract : Supplemental Digital Content is available in the text.